Multidisciplinary consensus: A practical guide for the integration of abiraterone into clinical practice. Issue 3 (17th August 2014) - Woo, Henry H; Begbie, Stephen; Gogna, Kumar; Mainwaring, Paul N; Murphy, Declan G; Parnis, Francis; Steer, Christopher; Davis, Ian D
Abstract Abiraterone improves survival, relieves pain, improves quality of life and extends time to prostate‐specific antigen (PSA) progression in patients with metastatic castration‐resistant prostate cancer (mCRPC). A consensus‐based guide for using abiraterone in patients with mCRPC has been developed by Australian clinicians with expertise in prostate cancer, based on their experience and supported by published data. Recommendations were developed for eight key topics: abiraterone administration; steroid administration and duration of use; concomitant medications and drug interactions; timing of testing and monitoring response; safety in different populations; potential toxicities; precautions and contraindications; and referral and multidisciplinary care. Abiraterone is taken orally in a fasting state. Symptoms associated with mineralocorticoid excess are managed by coadministration of low‐dose prednisone or prednisolone. Potassium levels, blood pressure and liver function need to be tested frequently during the early treatment phase. Response to treatment is monitored based on symptoms, radiological imaging and PSA levels. Potential adverse consequences of long‐term steroid therapy on bone and metabolic health need to be screened for and managed. Advanced prostate cancer is best managed by a multidisciplinary team and early referral should be considered. Questions about the potential use of abiraterone in early disease and in combination with other therapies are being addressed in ongoing clinical trials.